Why Do Traditional and Shadow Banks Coexist? - Lyonnet, Victor; Chrétien, Edouard (Review of Financial Studies, 2026)
Traditional and shadow banks interacted in similar ways in the 2007 and COVID-19 crises, when both assets and liabilities flew out of shadow banks and into traditional banks. We explain these facts in a model of the coexistence of traditional and shadow banks in which liabilities and assets flow from the former to the latter in good times, avoiding regulation, and move the other way in a crisis, alleviating fire sales. The model sheds light on how regulations for traditional banks have (unintended) consequences on the shadow banking sector.